Comparative Analysis of Microbial Species and Multidrug Resistance Patterns Associated with Lower Urinary Tract Infections in Preterm and Full-Term Births - Felix Bratosin; Roxana Folescu; Pavel Krupyshev; Zoran Laurentiu Popa; Cosmin Citu; Adrian Ratiu; Ovidiu Rosca; Adrian Cosmin Ilie (Microorganisms, 2024)
The rise of multidrug-resistant organisms has significantly complicated the clinical management of urinary tract infections (UTIs), particularly in the context of pregnancy. This study aimed to identify and analyze the significant differences in microbial species and multidrug resistance patterns associated with UTIs in preterm versus full-term births, determine the bacterial species significantly associated with preterm birth, and describe the antibiotic resistance patterns affecting pregnant women with UTIs. This case–control study was conducted in western Romania and focused on pregnant women with UTIs admitted from 2019 to 2023. Data were retrospectively collected from 308 patients with positive cultures. Statistical analyses, including the Chi-square test, Fisher’s exact test, and logistic regression models, were employed to compare the proportions of microbial species and resistance patterns between preterm (n = 126) and full-term (n = 182) birth groups and identify factors independently associated with preterm birth. The study found no significant differences in demographic or lifestyle factors between the groups. However, significant differences were observed in several infection and inflammation markers. The median white blood cell count was higher in the preterm group (12.3 vs. 9.1, p = 0.032), and the median C-reactive protein level was significantly higher in the preterm group (18 vs. 7, p < 0.001). The preterm group exhibited a higher incidence of multidrug-resistant organisms, notably ESBL-producing organisms (19.8% vs. 4.4%, p < 0.001) and carbapenem-resistant Enterobacteriaceae (4.8% with p = 0.003). Notably, the resistance to amoxicillin was significantly higher in the preterm group (20.6% vs. 6.6%, p < 0.001). Significant bacterial associations with preterm births included Group B Streptococcus (OR 2.5, p = 0.001) and Enterobacter spp. (OR 1.8, p = 0.022). The study confirmed significant differences in microbial species and multidrug resistance patterns between UTIs associated with preterm and full-term births. The higher prevalence of certain bacteria and increased resistance to commonly used antibiotics in the preterm group underscore the need for tailored antimicrobial therapies and robust microbial identification in managing UTIs during pregnancy.